2006
DOI: 10.1088/0957-4484/17/5/031
|View full text |Cite
|
Sign up to set email alerts
|

Localized cathodoluminescence of individual ZnSe nanorods

Abstract: Highly oriented ZnSe nanorods were grown on a ZnSe epilayer on GaAs(001) substrate by metalorganic chemical vapour deposition without any introduced catalysts. Cathodoluminescence spectra and images of individual nanorods, projecting from the buffer layer, were obtained at various temperatures down to 4.5 K in a scanning electron microscope. They show that the luminescence of the nanorods is localized, with the near band edge and deep level related emissions originating predominantly from their interior and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
3
12
0
Order By: Relevance
“…Near the band edge, the PL spectrum is dominated by the free‐exciton emission peak at 2.808 ± 0.001 eV, denoted by FX, and donor‐bound exciton emission peak at 2.779 ± 0.001 eV, denoted by D 0 X. The peak position of the observed FX peak is in good agreement with the earlier reports . Adjacent to the D 0 X peak are two weaker peaks attributed to the D 0 X longitudinal‐optical (LO) phonon replicas at 2.748 ± 0.002 eV and 2.717 ± 0.003 eV, which are denoted by D 0 X‐LO and D 0 X‐2LO, respectively.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Near the band edge, the PL spectrum is dominated by the free‐exciton emission peak at 2.808 ± 0.001 eV, denoted by FX, and donor‐bound exciton emission peak at 2.779 ± 0.001 eV, denoted by D 0 X. The peak position of the observed FX peak is in good agreement with the earlier reports . Adjacent to the D 0 X peak are two weaker peaks attributed to the D 0 X longitudinal‐optical (LO) phonon replicas at 2.748 ± 0.002 eV and 2.717 ± 0.003 eV, which are denoted by D 0 X‐LO and D 0 X‐2LO, respectively.…”
Section: Resultssupporting
confidence: 90%
“…Figure b also shows two broad deep‐level emission (DLE) bands located at ∼2.31 eV (DLE1) and ∼1.97 eV (DLE2) following TPE at low temperatures. Although the presence of such DLE bands have been previously reported in both bulk and nanoscale ZnSe materials, the origins and the dynamics of these DLEs remain poorly understood . DLE2 is usually observed from low temperatures to room temperature in doped or nominally undoped ZnSe materials.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous cathodoluminescence measurements of single CdSe needles, 5 ZnSe nanorods 6 and ZnO nanowires 7 have indicated that morphology can influence their emission. Here, direct optical imaging of a number of single VLS-prepared CdS nanowires reveal two distinct types of emission: a spectral band emitting at energies associated with free and bound exciton emission from CdS, and spatially localized states at lower energy which we relate to morphological irregularities of the nanowires.…”
mentioning
confidence: 99%